OPTIMALISASI PERTANIAN DENGAN MEMANFAATKAN LAHAN PEKARANGAN DAN BUDIDAYA BIBIT POHON DURIAN DI DESA WAJAGESENG, KECAMATAN KOPANG, KABUPATEN LOMBOK TENGAH. - Putra, Urief Arsani Atma; Aprillia, Dea; Andika, Puput; Wardani, Linda Noviantika; Ilhamsyah; Amalia, Dina; Pramadani, Intha Daefa; Asnawi, Hammam Adian; Ningrum, Safitri Ade; Arsana, I Dewa Putu; Putra, I Nyoman Nugraha Ardana (Jurnal Wicara, 2024)
Wajageseng Village is one of the villages in the Kopang District area. Based on the official website of the Central Lombok Regency Statistics Agency, in Kopang District, Wajageseng village has an area of ​​13 km2. The majority of the population works as farmers. Therefore, the KKN student group carried out activities by utilizing empty land chosen by residents, especially in home gardens. The aim of implementing this KKN activity is to realize the theme of Advanced and Sustainable Agriculture in Wajageseng Village. There are 3 activities carried out, namely (1) using empty land to cultivate durian seeds (2) making organic fertilizer to fertilize durian tree seeds (3) socializing organic fertilizer for durian tree seeds. The result of this activity is that the people of Wajageseng Village are able to make optimal use of their yard land so they can enjoy the desired results. Apart from that, by making organic fertilizer from goat kohe, it is also hoped that the community will be able to utilize goat manure waste and there will be socialization on making organic fertilizer which aims to enable people to make their own organic fertilizer at home. The results of the activities above show that this KKN activity has been able to answer several problems that exist in Wajageseng village regarding the use of house yard land for cultivating plants in order to realize advanced and sustainable agriculture.